MOTIVASI SISWA SELAMA PEMBELAJARAN DARING (ONLINE) DI SMP KARTIKA PEKANBARU - Kirana Yulni Syahputri; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine student motivation during online learning at Junior High School Kartika Pekanbaru. Motivation is seen from two factors, namely external and internal factors of students. Of course, the students have different abilities that are influenced by factors from outside and within the students themselves. This research was conducted at Kartika Junior High School Pekanbaru precisely on Jalan Dr.Sutomo No.65 Pekanbaru. To obtain the results of the study, the author used the Descriptive Quantitative method with a total of 96 respondents. The determination of the number of samples is by using the saturated sample method, namely all members of the population are used as samples. Data collection techniques through questionnaires and documentation carried out by researchers to students as samples. Based on the results of respondents' responses through the distribution of questionnaires, the results of this study show that respondents responses regarding online learning are mostly good and the motivation for student learning during online learning is mostly quite high judging from the results of respondents answers. Keywords : Motivation,Online Learning